Anterior pelvic plane tilt poorly estimates the sagittal body alignment due to internal rotation of innominate bone. Issue 3 (8th June 2020) - Ueno, Takuro; Kabata, Tamon; Kajino, Yoshitomo; Inoue, Daisuke; Ohmori, Takaaki; Yoshitani, Junya; Ueoka, Ken; Yamamuro, Yuki; Tsuchiya, Hiroyuki
Abstract: This study investigated the influence of the rotation of innominate bone on anterior pelvic plane (APP) tilt, the angle formed by the APP, and coronal plane of the body to determine whether the provision of proper information about the sagittal balance of the body by the value of the APP tilt (APPT). In total, 244 patients (171 females, 73 males) who were candidates for total hip or knee arthroplasty, periacetabular osteotomy, or shelf arthroplasty were included. The rotational angle of the innominate bone was quantified using computed tomography images at the level of the anterior superior, and anterior inferior iliac spine, and ischiopubic portion. Clustering analysis was performed to identify subtypes of innominate bone rotation. High, intermediate, and low internal rotational alignment groups were identified in females, characterized by rotational angles. Males were treated as one group, and no intergroup differences were observed in sacral slope (SS) and pelvic incidence. However, intergroup differences in APPT were found, indicating a variation in APPT irrespective of sagittal body balance. A negligible relationship between SS and APPT was observed in the high‐internal‐rotation group, intermediate‐internal‐rotation group, and male group, whereas a moderate correlation found in the low‐internal‐rotation group ( r = .59). The results could suggest surgeons that the value of the APPT provides no information on the sagittal balance; therefore, it may be ignored for acetabular component positioning during preoperative planning for total hip arthroplasty. Abstract : The great variation in rotational alignment in innominate bones exists between individuals. Due to this variation, the relative position of the anterior superior iliac spines and pubic symphysis within the pelvis also varies greatly. Consequently, internal rotation, especially of the superior ilium, is a potent factor, which has led anterior pelvic tilt to be misinterpreted as indicating an anterior tilting pelvic orientation and a negligible relationship between sacral slope and anterior pelvic plane tilt.